Uma versão abstrata do teorema de Cauchy-Kowalevski - Ferreira, Danilo de Jesus (2013)
Our main goal in this work is to present an abstract version of Cauchy-Kowalevski theorem and use it to solve the periodic Cauchy problem for the Camassa-Holm equation.